Energy analysis of intact granite based on test while drilling under different confining stresses and drilling parameters - Tang, Hua; Liang, Dong-Cai; Wu, Zhen-Jun; Cheng, Xu (Frontiers in Earth Science, 2023)
The rock properties are related to the stress environment and dynamic disturbance during construction, and the testing-while-drilling-technique was used for evaluation of rock properties. However, the related research ignored the influences of stress environment and drilling parameters. In this paper, triaxial compression tests and laboratory drilling tests under different confining stresses and drilling parameters were conducted for intact granite. The static part of elastic energy and drilling specific energy (dynamic energy) of rock were calculated by using linear energy storage theory and rock breaking energy theory, respectively. The results showed that the static elastic energy increased with the increase of confining stress, while the drilling specific energy was opposite. An energy analysis method based on the drilling process was proposed. A total energy index was defined as the sum of static elastic energy and dynamic elastic energy. For the same rock, the total energy is a constant value under the same drilling parameters. The influences of drilling parameters on the total energy was quantified by a dynamic load influence factor. The new energy analysis method was verified by drilling test, which provided a new energy index for evaluating rock properties. The potential application of the energy analysis method in stress estimation was explored.